IMPLICATIONS OF PRIVATE MILITARY COMPANIES ON GEOPOLITICS AND GLOBAL SECURITY - Lazarević, Dajana (The Policy of National Security, 2025)
Private military companies are part of a fairly developed private security sector, present all over the world and engaged in various jobs. Apart from participation in war conflicts, which are most often associated with them, the services offered by private military companies are different: from the provision of energy sources to the collection of intelligence data, but also the training of military personnel, military logistics and the supply of armed forces with assets. This paper examines the history of private military companies' existence and the use of mercenaries in war conflicts. The moral and material circumstances of their engagement, the achieved results and their impact on geopolitics and global security, as well as the international legal regulations of their engagement, are considered. Also, the work examines the “grey zone” of activities of private military companies, accusations of mistreatment and murder of civilians, tax evasion, drug dealing and human trafficking, for which they are most often accused. However, although their work is always accompanied by numerous scandals and accusations of the aforementioned crimes, court epilogues are usually absent. The paper looks at the participation of private military companies in the conflicts in FR Yugoslavia, as well as their presence in AP Kosovo and Metohija and its consequences.
Keywords: private military companies; geopolitics; global security; international relations; private security sector